Buckling Behavior Of Axially Compressed Cylindrical Shells: Comparison Of Theoretical And Experimental Data - Olawale Friday, Ifayefunmi (Elsevier Ltd., 2016)
This paper examines the buckling of short mild steel cylindrical shells subjected to axial compression. Cylinders were joined together using Metal Inert Gas (MIG) welding process with radius-to-thickness ratio, R/t, ranging from 25 to 100. The axial length of the specimens were assumed to be 111.8 mm. Past result on axially compressed cylinder machined using Computer Numerically Controlled (CNC) machining is compared with fresh experimental results on MIG manufactured axially compressed cylinder. The paper contains a comparison between theoretical predictions, ABAQUS FE results and experimental data for axially compressed cylinder. Details about material testing and collapse test are provided. As compared to the CNC machined specimen, results indicates that there is a good agreement between theoretical prediction, ABAQUS FE results and experimental data for MIG manufactured cylinder with radius-to-thickness ratio, R/t ranging from 25 to 100, with difference ranging between -7% and +2%.